Examining the Impact of Islamic Banking on Indonesia Economic Growth: Short- and Long-term Analysis - Ayu Lestari, Mey (Journal International Economic Sharia, 2024)
Objective; This study examines the relationship between Islamic financial development and economic growth in Indonesia, with a focus on the short-term and long-term impacts. The research aims to understand the role of Islamic banking in driving the country's economic performance.Methods; A quantitative approach was used, employing time series data from 1992 to 2024. Multiple regression analysis was applied to assess the relationship between Islamic banking indicators, such as total assets, financing, and non-performing financing (NPF), and economic growth, measured by GDP growth.Results; The findings indicate that Islamic financial development significantly contributes to Indonesia's economic growth, with both short-term and long-term effects. Non-performing financing (NPF) was found to be inversely related to growth, while total assets and financing had positive effects.Novelty; This study fills a gap in the literature by exploring the specific role of Islamic financial institutions in an emerging market context, particularly in Indonesia, where Islamic banking is growing rapidly. Research Implications; The results suggest that policy-makers should enhance Islamic financial sector development and address NPF to support sustainable economic growth. Future studies could investigate the impact of different financial instruments within the Islamic banking sector.